In-plane strength enhancement of laminated composites via aligned carbon nanotube interlaminar reinforcement. (14th September 2016) - Guzman de Villoria, R.; Hallander, P.; Ydrefors, L.; Nordin, P.; Wardle, B.L.
Abstract: Aerospace-grade unidirectional carbon fiber laminate interfaces are reinforced with high densities (>10 billion fibers per cm 2 ) of aligned carbon nanotubes (A-CNTs) that act as nano-scale stitches. Such nano-scale fiber reinforcement of the ply interfaces has been shown to increase interlaminar fracture toughness and here we show that laminate in-plane strengths are also increased. Delamination damage modes associated with pre-ultimate failure are suppressed in the in-plane loaded laminates, significantly increasing load-carrying capability: tension-bearing (bolt pull out) critical strength by 30%, open-hole compression ultimate strength by 14%, and L-section bending energy and deflection by more than 25%. No increase in interlaminar or laminate thickness is observed due to the A-CNTs, but rather the ∼10 nm diameter carbon nanotubes interdigitate between carbon fibers in the adjacent laminae, i.e., the observed reinforcement is not due to formation of a thicker interlayer. These increases in substructural in-plane strengths are in stark contrast to degradation that typically occurs with existing 3D reinforcement approaches such as stitching, weaving and z-pinning.